THE EFFECT OF ECONOMIC STATUS AND MOTOR MATURITY ON THE PERFORMANCE OF FUTSAL ATHLETES AT SMK CINTA KASIH TZU CHI: THE ROLE OF SELF-EFFICACY AS MEDIATION - Galih Yoga Purnama; Endang Rini Sukamti; Fauzi; Abdul Alim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of economic status and motor maturity on futsal athletes performance through the mediation of self-efficacy. The research design employed a quantitative cross-sectional approach using a census method on 30 male athletes from SMK Cinta Kasih Tzu Chi. Data analysis utilized mediation regression based on the Hayes PROCESS Macro Model 4 with bootstrapping procedure 5,000 times to ensure the accuracy of astimates in a small sample size. Instrument reliability was confirmed through Cronbach's Alpha coefficient of 0.89 (self-efficacy) and an the Intraclass Correlation Coefficient (ICC) of 0.91 (performance). The analysis results showed that economic status did not have significant direct effect on performance (β=0.082; p=0.651) but exerts a significant indirect effect through self-efficacy (full mediation; IE=0.231; 95% CI [0.054; 0.487]). Motor maturity significantly affects performance both directly (β=0.389; p=0.004) and indirectly through self-efficacy (partial mediation; IE=0.175; 95% CI [0.031; 0.389]). The overall model exhibits high predictive power (R²=0.658). These findings confirm that self-efficacy is an essential cognitive mechanism capable of mitigating limitations in socioeconomic and biological capital to achieve tangible performance in futsal.